2003
DOI: 10.1021/jp0269367
|View full text |Cite
|
Sign up to set email alerts
|

The Relation between Bond Lengths and Dissociation Energies of Carbon−Carbon Bonds

Abstract: Bond lengths (r, Å) of typical carbon-carbon bonds correlate linearly with bond dissociation energies (BDEs) in the full range of single, double, triple, and highly strained bonds, with BDEs ranging from 16 to 230 kcal mol -1 . The equation is r ) 1.748-0.002371(BDE), tested with 41 typical carbon-carbon bonds, ranging in length from 1.20 to 1.71 Å. This sets a maximum bond length limit of 1.75 Å for carbon-carbon bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
123
2
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(139 citation statements)
references
References 13 publications
7
123
2
4
Order By: Relevance
“…Beyond this point, the ultimate separation occurs when the interatomic distance between the last two bonded C-C atoms exceeds 1.75 Å. From the literature [43], it was found that, 1.75 Å is the maximum possible bond length between the two carbon atoms which is found consistent with the current observation.…”
Section: Simulation Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Beyond this point, the ultimate separation occurs when the interatomic distance between the last two bonded C-C atoms exceeds 1.75 Å. From the literature [43], it was found that, 1.75 Å is the maximum possible bond length between the two carbon atoms which is found consistent with the current observation.…”
Section: Simulation Analysissupporting
confidence: 91%
“…Although the quantitative measure of separation distance [43] of C-C bond of 1.75 Å provide confidence in the MD simulation, authors also conducted an evaluation of the modulus of elasticity from the loading and unloading curve shown in Fig. 11.…”
Section: Simulation Analysismentioning
confidence: 99%
“…Angewandte empirische Bindungslänge-Bindungsstärke-Korrelationen, [148] die üblicherweise exzellent für Kohlenwasserstoffe greifen: Vonk urzen Bindungen denkt man, dass sie stärker sind als lange Bindungen, [149] wie bereits 1960 von Pauling [150] und später erneut beschrieben. [148] Die Herstellung einer Serie gekuppelter Diamantoid(hetero)dimere brachte im Falle des 2-(1-Diamantyl) [121]tetramantans( Abbildung 8, links) sterisch stark überfrachtete Strukturen mit außerordentlich langen zentralen C-C-Bindungen von bis zu 1.707 h ervor.…”
Section: London'sche Dispersionunclassified
“…[148] Die Herstellung einer Serie gekuppelter Diamantoid(hetero)dimere brachte im Falle des 2-(1-Diamantyl) [121]tetramantans( Abbildung 8, links) sterisch stark überfrachtete Strukturen mit außerordentlich langen zentralen C-C-Bindungen von bis zu 1.707 h ervor. Dies ist die längste publizierte C-C-Bindung in einem reinen Alkan (längere C-C-Bindungen von bis zu 1.78 wurden für Strukturen mit Heteroatomen beschrieben [151] ).…”
Section: London'sche Dispersionunclassified
“…Based on a database study, Zavitsas expected that the covalent bond dissociation energy (BDE) would be diminished at a distance greater than 1.75 ¡ by assuming a negative-sloped linear correlation between BDE and the bond distance. 3 Adcock reported that the shortest nonbonded C£C contact was 1. 8 ¡, 4 which suggests that the CC bond length might have a limit of around 1.8 ¡.…”
Section: ¹1mentioning
confidence: 99%